Ultra-processed family foods in Australia: nutrition claims, health claims and marketing techniques - Pulker, C.; Scott, Jane; Pollard, C. (Cambridge University Press, 2017)
Copyright © The Authors 2017 This is an Open Access article, distributed under the terms of the Creative Commons Attribution licence (http://creativecommons.org/licenses/by/4.0/), which permits unrestricted re-use, distribution, and reproduction in any medium, provided the original work is properly cited. Objective: To objectively evaluate voluntary nutrition and health claims and marketing techniques present on packaging of high-market-share ultra-processed foods (UPF) in Australia for their potential impact on public health. Design: Cross-sectional. Setting: Packaging information from five high-market-share food manufacturers and one retailer were obtained from supermarket and manufacturers’ websites. Subjects: Ingredients lists for 215 UPF were examined for presence of added sugar. Packaging information was categorised using a taxonomy of nutrition and health information which included nutrition and health claims and five common food marketing techniques. Compliance of statements and claims with the Australia New Zealand Food Standards Code and with Health Star Ratings (HSR) were assessed for all products. Results: Almost all UPF (95 %) contained added sugars described in thirty-four different ways; 55 % of UPF displayed a HSR; 56 % had nutrition claims (18 % were compliant with regulations); 25 % had health claims (79 % were compliant); and 97 % employed common food marketing techniques. Packaging of 47 % of UPF was designed to appeal to children. UPF carried a mean of 1·5 health and nutrition claims (range 0–10) and 2·6 marketing techniques (range 0–5), and 45 % had HSR=3·0/5·0. Conclusions: Most UPF packaging featured nutrition and health statements or claims despite the high prevalence of added sugars and moderate HSR. The degree of inappropriate or inaccurate statements and claims present is concerning, particularly on packaging designed to appeal to children. Public policies to assist parents to select healthy family foods should address the quality and accuracy of information provided on UPF packaging.